2022
DOI: 10.3389/fsufs.2022.996586
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in soil water nitrate beneath a perennial grain crop compared to an annual crop rotation on sandy soil

Abstract: Nitrate (NO3--N) leaching into groundwater as a result of high nitrogen (N) fertilizer rates to annual crops presents human health risks and high costs associated with water treatment. Leaching is a particularly serious concern on sandy soils overlying porous bedrock. Intermediate wheatgrass (IWG) [Thinopyrum intermedium (Host.) Barkw. & D.R. Dewey], is a perennial grass that is being bred to produce agronomically and economically viable grain, which is commercially available as Kernza®. Intermediate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Standing root stocks were 3-6 and 6-10 times greater in IWG-1 and IWG-2, respectively, compared with spring wheat when averaged across growth period, in line with studies showing that IWG root stocks between 0 and 15 cm were 4-25 times greater in IWG than annual row crop monocultures including soybean and maize (Rakkar et al, 2023Reilly et al, 2022. The larger standing root stocks in IWG were associated with generally greater new root production rates (except between elongation and maturity) compared with wheat, with wheat on average maintaining new root production rates of around 2 g m −3 day −1 in both 2020 and 2021.…”
Section: Standing Root Stocks and New Root Production In Annual And P...supporting
confidence: 82%
See 1 more Smart Citation
“…Standing root stocks were 3-6 and 6-10 times greater in IWG-1 and IWG-2, respectively, compared with spring wheat when averaged across growth period, in line with studies showing that IWG root stocks between 0 and 15 cm were 4-25 times greater in IWG than annual row crop monocultures including soybean and maize (Rakkar et al, 2023Reilly et al, 2022. The larger standing root stocks in IWG were associated with generally greater new root production rates (except between elongation and maturity) compared with wheat, with wheat on average maintaining new root production rates of around 2 g m −3 day −1 in both 2020 and 2021.…”
Section: Standing Root Stocks and New Root Production In Annual And P...supporting
confidence: 82%
“…In terms of environmental health, the agronomic practices and physiological traits inherent to perennial crops confer a suite of ecological benefits on agricultural landscapes. When compared to annual crops, the reduced tillage and diminished fertilizer inputs of perennial cropping systems reduce soil nitrate leaching (Jungers et al, 2019;Reilly et al, 2022), enhance nutrient uptake (Sprunger et al, 2018a), and promote the formation of stable soil aggregates (Rakkar et al, 2023;Tiemann & Grandy, 2015). Physiological differences in carbon (C) uptake and partitioning between perennial and annual grains (Woeltjen, 2023) such as greater photosynthetic activity (Jaikumar et al, 2013(Jaikumar et al, , 2016, higher belowground C allocation to roots (Sainju et al, 2017), and extensive root production in perennial grains also contribute to the development of more robust soil microbial communities (Audu et al, 2022;Liang et al, 2012;McKenna et al, 2020;Tiemann & Grandy, 2015) and increase the potential sequestration of atmospheric CO 2 in belowground C pools.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of water that is unavailable to annual crops can reduce nutrient losses to surface water and groundwater. Research has shown that intermediate wheatgrass grown for grain can reduce NO 3 leaching to groundwater—thus protecting rural drinking water sources while generating an economic return for farmers (Huddell et al., 2023; Jungers et al., 2019; Reilly et al., 2022). Similarly, Randall and Mulla (2001) showed that subsurface field drainage volume and nitrate N losses were 30–50 times higher beneath annual crops compared with perennial crops.…”
Section: Current State Of Perennial Agricultural Landscapesmentioning
confidence: 99%
“…Pastures and forage crops are well known for their ecosystem service benefits (e.g., soil health), and have large ranges that encompass many different cropping systems (Aponte et al, 2019;Martin et al, 2020;Teixeira et al, 2021). The perennial grain Kernza is one example of the potential for perennial crops to improve soil quality and water regulation (Audu et al, 2022;Rakkar et al, 2023;Reilly et al, 2022;van der Pol et al, 2022) perennials to provide these ecosystem benefits is one reason they are a powerful climate adaptation tool. Perennials also have a longer growing season than annuals, thus allowing these crops to capture and utilize water that is available outside the typical annual crop growing season (Vico & Brunsell, 2018).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation